CORRELATION BETWEEN MANNITOL INTERVENTION AND ELECTROLYTE IMBALANCE IN TRAUMATIC BRAIN INJURY PATIENTS OF REGIONAL GENERAL HOSPITAL OF WEST NUSA TENGGARA PROVINCE - Narayana, I Gusti Ngurah Wira; Priyanto, Bambang; Rasyidi, Rohadi Muhammad; Ansyori, Maz Isa; Zuhan, Arif; Indriawan, Ramses; nurchalamsah, Wahyu; Maulana, Akhada; Putrawan, Sanditias; Fatrahady, Lalu Shaktisila (Lombok Health And Science Journal, 2022)
Background: Traumatic brain injury (TBI) is a commonly occurring injury following traffic accident. The most common complication following TBI is electrolyte imbalance and might be happen due to mannitol use. This research aims to know the correlation between mannitol intervention and electrolyte imbalance (natrium, kalium and chloride) in TBI patients of Regional General Hospital of West Nusa Tenggara Province. Methods: This is a retrospective research with cross–sectional design. This research was done in Regional General Hospital of West Nusa Tenggara Province. Samples were collected by medical records of TBI patients from 2018 to 2019 which had met the inclusion criteria and then tested with correlation comparative test. Results: From 160 samples that were obtained, 146 samples had electrolyte data, then categorized into those who were given mannitol (73,29%) and those who were not given mannitol (26,71%). The most common electrolyte imbalance was chloride (70,55%) which in hyperchloremia condition, followed by kalium (30,82%) with hyperkalemia and natrium (28,08%) with hyponatremia. Mannitol is most commonly given for one day and has the mean intervention of 2.6 days. Length of mannitol intervention and electrolyte levels were not normally distributed. There was no statistically significant difference between mannitol intervention and electrolyte imbalance (p=1.000, p=1.000, p=0.481) and length of stay on patients with no mannitol intervention and electrolyte imbalance (p=0,856, p=0,303, p=0,347). Conclusion: This research shows no correlation between the length of mannitol intervention and electrolyte imbalance (represented by natrium, kalium, and chloride) in TBI patients of Regional General Hospital of West Nusa Tenggara Province. Keywords: mannitol intervention, electrolyte imbalance, traumatic brain injury.